Determinants of Profitability in State-Owned Islamic Banks: Evidence from Indonesia, Malaysia, and Brunei Darussalam - Fathan Munim; Firman (Jurnal Internasional Ekonomi Islam, 2026)
Objective: This study aims to examine the factors that determine the profitability of state Islamic banks (Indonesia, Malaysia, and Brunei Darussalam). Method: This research uses an associative quantitative approach. The data used comes from State-Owned Islamic Banks in 3 countries (Indonesia, Malaysia, and Brunei Darussalam) from 2015 to 2024, sourced from Bank Syariah Indonesia (BSI), Bank Islam Brunei Darussalam (BIBD), and Bank Islam Malaysia Berhad (BIMB). The data were analyzed using panel data quantile regression in EViews. Result: This study found that NPF has a negative and significant effect on the ROE of state-owned Islamic banks, whereas CIR, CAR, and FDR have positive and significant effects on the ROE of state-owned Islamic banks. The second result shows that ROE, NPF, and CIR have a negative and significant effect on ROA, while CAR and FDR variables have a positive and significant effect on ROA. Based on the results of the quantile and Sobel regression tests, it is clear that NPF, CIR, CAR, and FDR variables influence the ROA of state-owned Islamic banks, either directly or through ROE. Implication: This study emphasizes the need to strengthen profitability risk-based policies among institutions in Indonesia, Malaysia, and Brunei Darussalam to enhance the competitiveness of state-owned sharia banks in the region. Originality or Novelty: The originality of this research lies in using Return on Equity (ROE) as a mediating variable and, at the same time, employing panel data quantile regression, where ROE mediates the relationship between the profitability of state-owned Islamic banks and Return on Assets (ROA).